Evaluasi Kinerja Penanggulangan Kelongsoran Lereng pada Timbunan Tinggi Menggunakan Bronjong Berbasis Analisis Plaxis V24.3.0: Studi Kasus Candisari, Kota Semarang - Nazala Trisnadyani; Nur Mukti Afiatillah; Lisa Fitriyana (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study evaluates the performance of gabion reinforcement in mitigating slope failure on a high embankment slope in Candisari, Semarang City, using finite element analysis based on PLAXIS V24.3.0. The research integrates field observations, laboratory geotechnical testing, and numerical simulation to investigate slope deformation behavior, safety factor characteristics, and hydro mechanical responses under varying groundwater conditions. The numerical model was developed using plane strain analysis with staged construction procedures and strength reduction factor methods to represent actual field conditions. The results indicate that the unreinforced slope experienced significant deformation and a critical safety factor associated with progressive failure mechanisms. The installation of gabion structures improved slope stability by reducing horizontal and vertical displacement, redistributing effective stress, and shifting the slip surface away from the critical zone. Variations in groundwater level significantly affected slope performance through increased pore water pressure and reduced effective stress conditions. The study confirms that gabion reinforcement provides effective structural resistance for high embankment slopes, although hydraulic sensitivity remains a controlling factor in long term stability performance.